2017
DOI: 10.1590/s0004-2803.201700000-01
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease: Outpatient Treatment Profile

Abstract: -Background -Crohn's disease and ulcerative colitis are the two major forms of inflammatory bowel disease. The incidence and prevalence of both conditions have increased and are progressively increasing. These diseases are frequently recurrent and clinically highly severe. In Brazil, the lack of epidemiological data related to such diseases has left these patients in a vulnerable state and contributed to increased morbidity. Objective -To describe the profiles of patients with inflammatory bowel disease treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
1
9
1
3
Order By: Relevance
“…In 11 studies, the greatest proportion of patients had extensive (pancolitis). 10 , 17 , 21 24 , 27 – 30 , 33 In a nationwide study in Mexico, which separated UC extension by age group, pancolitis was the most frequent extension of UC in children (64.4%), adult (62.2%) and elderly (57.7%) patients; distal/proctosigmoiditis was the second most frequent extension in children (22.2%), adult (24.8%) and elderly (26.8%) patients; and left-sided colitis was the least frequent extension in children (13.3%), adult (13.0%) and elderly (15.6%) patients. 27 , 28 In line with this, the highest proportion of patients (43%) had pancolitis in a study in Argentina.…”
Section: Resultsmentioning
confidence: 99%
“…In 11 studies, the greatest proportion of patients had extensive (pancolitis). 10 , 17 , 21 24 , 27 – 30 , 33 In a nationwide study in Mexico, which separated UC extension by age group, pancolitis was the most frequent extension of UC in children (64.4%), adult (62.2%) and elderly (57.7%) patients; distal/proctosigmoiditis was the second most frequent extension in children (22.2%), adult (24.8%) and elderly (26.8%) patients; and left-sided colitis was the least frequent extension in children (13.3%), adult (13.0%) and elderly (15.6%) patients. 27 , 28 In line with this, the highest proportion of patients (43%) had pancolitis in a study in Argentina.…”
Section: Resultsmentioning
confidence: 99%
“…[50]One study found a higher prevalence of left-sided colitis, higher mortality, and higher usage of biological agents in Mexican population than in Mexican-American population, supporting the role of environmental factors on clinical characteristics of IBD. [24] The larger case-series in LAC Countries are from 1946 to date are from Argentina [14,51,52], Barbados [13], Brazil [14,[53][54][55][56][57][58][59][60][61][62][63][64][65], Chile [66][67][68], Cuba [69], Peru [70,71], Puerto Rico [72][73][74][75] and Uruguay. [76][77][78] Most CD localizations were ileal-colonic and CD behavior was mostly inflammatory, followed by penetrant or stenotic.…”
Section: Discussionmentioning
confidence: 99%
“…Complementarily data have shown a higher prevalence among youngsters in recent years 1725. Unfortunately, in Brazil, epidemiological data are scarce and generally refer to the public health system, based on hospitalization records or records of patients who purchase high-cost medications through the government 2631. Although the main symptoms of the diseases are well-known in the literature, in Brazil up until now, there have been no studies on the main clinical signs and symptoms that could lead to investigation and diagnosis from the time of the onset of the symptoms to a defined diagnosis; in what way these diseases are present; which is the most frequent behavior; the associations of risk factors; what medical approaches have been attempted, and the incidence of complications over time.…”
Section: Introductionmentioning
confidence: 99%